Characteristics of malingered amnesia: Consequences of withholding vs. distorting information on later memory of a crime event - Bylin, Susanna; Christianson, Sven-Åke (Legal and criminological psychology, 2002)
Purpose. Perpetrators may be more motivated than other witnesses to withhold reporting crime‐related details that have a probative value for the police investigation. One strategy among suspects/perpetrators to absolve themselves from culpability is simply to feign memory impairment. The present study aimed to investigate how different kinds of simulation of memory impairment affect later genuine memory performance. Methods. Individuals were tested as perpetrators after having read a story about ‘themselves’ committing a violent crime. There were four groups and two test occasions. At the first test occasion, one group was tested on what they actually recalled, a second group was not tested at all, while the two remaining groups were asked to simulate memory impairment by making either omission errors (SIM OM) or commission errors (SIM COM). At the second test occasion, all groups responded genuinely. Results. Different kinds of simulation have different impact on later recall. Simulation by omission caused more detrimental effects than simulation by commission on free recall, while the reverse was true for responses to open‐ended questions. However, simulators showed no impairments on the multiple‐choice questions. Conclusions. Simulators' worse memory performance is discussed in terms of non‐rehearsal effects and retrieval‐induced forgetting. Regarding the open‐ended questions, misinformation effects might come into play.